THE ROLE OF RIGHTS AND OBLIGATIONS IN IMPROVING THE QUALITY OF HEALTH SERVICES: A MULTIDISCIPLINARY LITERATURE REVIEW - Gunawan Widjaja; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (CV. Adiba Aisha Amira, 2025)
This study aims to examine the role of rights and obligations of medical personnel and patients in improving the quality of health services through a multidisciplinary literature review. Rights and obligations that are carried out in a balanced manner have been proven to be the main foundation for the creation of harmonious, transparent, and trusting relationships between patients and medical personnel, thus having a positive impact on the quality of health services. However, implementation in the field still faces challenges such as inequality of access, limited infrastructure, and the development of digital technology that has not been fully regulated. Protection of patients' personal data, clarity of legal responsibility in digital services, and continuous education are important issues that need attention. Strengthening regulations, increasing digital literacy, and cross-sector collaboration are needed so that rights and obligations can be carried out optimally, so that fair, quality, and adaptive health services can be realised.